IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI DI KOTA PALU - Abdullah, Dewi Cahyawaty (Katalogis, 2018)
The problem that often occurred in the implementation of early childhood education (ECE) was there were still many ECE apparatuses and institutions that were not aware of the ECE policy, so this study aimed to analyze the implementation of early childhood education policy in Palu City and it was expected to provide an overview of the implementation of the ECE policy. This study used qualitative research to find out the facts and phenomena that occurred associated with the implementation of the ECE policy. The author used the indicators of Edward III, namely: communication, implementer attitude, resources, and bureaucratic structure. Informants in this study were those deemed to know and be involved in the policy implementation.Data used were primary data which was obtained directly from the informants and secondary data which was obtained indirectly. Data were collected through interviews, observations, and documentation. Data analysis consisted of three phases: data reduction, data presentation, and conclusion. The results show that the implementation of the ECE policy in Central Sulawesi had not been optimal:from Communication aspect, there were still officials who did not know the contents of the ECE policy; from Attitude aspect, there was still discrimination from the employees; from Resources aspect, there were apparatus resourcesof Palu City Department of Education and Culture particularly of the Early Childhood, Non-Formal, and Informal (PendidikanAnakUsiaDini, Non-Formal, dan Informal – PAUDNI) Divisionwho hadskills and reliabilities, but not all had the same opportunity to be a reliable employees, although there were facilities provided by the Department. While its bureaucracy structure had been very good, but there were still employees who were not aware of their duties and functions as shown at the bureaucracy structure board.